Improved Precision-Cut Liver Slice Cultures for Testing Drug-Induced Liver Fibrosis - Dewyse, Liza; De Smet, Vincent; Verhulst, Stefaan; Eysackers, Nathalie; Kunda, Rastislav; Messaoudi, Nouredin; Reynaert, Hendrik; van Grunsven, Leo A. (Frontiers in Medicine, 2022)
In vitro models of human liver disease often fail to mimic the complex 3D structures and cellular organizations found in vivo. Precision cut liver slices (PCLS) retain the complex physiological architecture of the native liver and therefore could be an exceptional in vitro liver model. However, the production of PCLS induces a spontaneous culture-induced fibrogenic reaction, limiting the application of PCLS to anti-fibrotic compounds. Our aim was to improve PCLS cultures to allow compound-induced fibrosis induction. Hepatotoxicity in PCLS cultures was analyzed by LDH leakage and albumin secretion, while fibrogenesis was analyzed by qRT-PCR and western blot for HSC activation markers and collagen 6 secretion by ELISA. We demonstrate that supplementation of 3 mm mouse PCLS cultures with valproate strongly reduces fibrosis and improves cell viability in our PCLS cultures for up to 5 days. Fibrogenesis can still be induced both directly and indirectly through exposure to TGFβ and the hepatotoxin acetaminophen respectively. Finally, human PCLS cultures showed similar but less robust results. In conclusion, we optimized PCLS cultures to allow for drug-induced liver fibrosis modeling.